2003
DOI: 10.1590/s0034-89102003000500022
|View full text |Cite
|
Sign up to set email alerts
|

A circuncisão masculina e a transmissão heterossexual do HIV

Abstract: ResumoDesde os primeiros anos da epidemia de Aids, grandes diferenças geográficas na prevalência de infecção pelo HIV foram registradas entre países vizinhos e regiões vizinhas dentro de um mesmo país na África subsaariana. Tais diferenças não podiam ser completamente explicadas por fatores como o comportamento sexual e o uso de preservativos. Um acúmulo de dados epidemiológicos vem mostrando que a circuncisão masculina desempenha um efeito protetor contra a aquisição heterossexual do HIV pelo homem na África … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although this figure by no means should be regarded as an estimate of the frequency of male circumcision in the overall population, it certainly suggests a low prevalence of male circumcision among residents of inner cities of the State. The uncircumcised status has been shown to be a major determinant of HIV transmission, mainly in African countries 5 . Studies on the prevalence of male circumcision in Brazil and on whether it is associated with viral spread among the heterosexual population are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Although this figure by no means should be regarded as an estimate of the frequency of male circumcision in the overall population, it certainly suggests a low prevalence of male circumcision among residents of inner cities of the State. The uncircumcised status has been shown to be a major determinant of HIV transmission, mainly in African countries 5 . Studies on the prevalence of male circumcision in Brazil and on whether it is associated with viral spread among the heterosexual population are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…TP appears tangentially in three studies and only one study addressed circumcision. The low interest in the issue of circumcision in the MSM population might be related to the low effectiveness of the method in male sexual intercourse or penetrating anal practices [75][76][77] . Detailed information about the studies is found in Table 4.…”
Section: Resultsmentioning
confidence: 99%